S-1 salvage chemotherapy for stage IV thymic carcinoma: a study of 44 cases - Wang, Chang-Lu; Gao, Lan-Ting; Lv, Chang-Xing (Journal of Thoracic Disease, 2019)
Background: Thymic carcinoma (TC) is a rare mediastinal tumor, and patients with stage IV TC have a poor prognosis. No optimal chemotherapeutic regimen has yet been established. In this study, we evaluated the efficacy and safety of S-1 as a salvage mono-therapy in stage IV TC. Methods: Patients with histologically confirmed stage IV TC were enrolled in this study when front-lined chemotherapy failed. S-1 capsules were orally taken twice a day. The daily dose was prescribed in three levels (80, 100, 120 mg) based on body surface area (BSA). One cycle of treatment consists of 4 weeks of drug use and 2 weeks of rest. The cycle was repeated until tumor progressed or intolerable toxicity occurred. The response rate, progression-free survival (PFS), overall survival (OS), and toxicity were evaluated. Results: Forty-four patients with stage IV TC were included between January 2013 and July 2017. Squamous cell carcinoma accounted for 84% of cases (37/44). There were 22 males and 22 females with a median age of 57 years (27–78 years). S-1 was prescribed at a dose of 80 mg for 18 (41%) patients, 100 mg for 17 patients (38%), and 120 mg for 9 patients (21%). The median number of cycles of administrated per patient was 3 [1–32]. Among 44 patients, 13 (30%) achieved a partial response, 22 (50%) remained stable disease, and 9 (20%) showed a rapid progression. With a median follow-up time of 14 months, the median PFS and OS of the whole group were 6 (95% CI, 7.0–13.9) months and 15 (95% CI, 13.2–21.6) months, respectively. For the 13 patients who showed response to S-1, the median PFS was 22 (95% CI, 15.5–30) months. Anorexia was the most common side effect, but all cases were mild. Other toxicities of grade ≥3 were bone marrow suppression (n=6) and rash (n=1). No drug-related deaths occurred. Conclusions: S-1 is a safe and effective treatment for stage IV TC as a salvage monotherapy. It is especially effective in disease control when the tumor shows response to S-1.